Correlation between bone mineral density and serum trace elements in response to supervised aerobic training in older adults - Alghadir AH (Dove Medical Press, 2016)
Ahmad H Alghadir,1 Sami A Gabr,1,2 Einas S Al-Eisa,1 Muaz H Alghadir3 1Rehabilitation Research Chair, College of Applied Medical Sciences, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Department of Anatomy, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 3Department of Orthopedics, King Fahad Medical City, Riyadh, Kingdom of Saudi Arabia Background: Life style and physical activity play a pivotal role in prevention and treatment of osteoporosis. The mechanism for better bone metabolism and improvement of physical disorders is not clear yet. Trace minerals such as Ca, Mn, Cu, and Zn are essential precursors for most vital biological process, especially those of bone health.Objective: The main target of this study was evaluating the effective role of supervised aerobic exercise for 1 hour/day, 3 days/week for 12 weeks in the functions of trace elements in bone health through measuring bone mineral density (BMD), osteoporosis (T-score), bone markers, and trace element concentrations in healthy subjects aged 30–60 years with age average of 41.2±4.9.Methods: A total of 100 healthy subjects (47 males, 53 females; age range 30–60 years) were recruited for this study. Based on dual-energy x-ray absorptiometry (DEXA) scan analysis, the participants were classified into three groups: normal (n=30), osteopenic (n=40), and osteoporotic (n=30). Following, 12 weeks of moderate aerobic exercise, bone-specific alkaline phosphatase (BAP), BMD, T-score, and trace elements such as Ca, Mn, Cu, and Zn were assessed at baseline and post-intervention.Results: Significant improvement in serum BAP level, T-score, and BMD were observed in all participants following 12 weeks of moderate exercise. Participants with osteopenia and osteoporosis showed significant increase in serum Ca and Mn, along with decrease in serum Cu and Zn levels following 12 weeks of aerobic training. In control group, the improvements in serum trace elements and body mass index were significantly linked with the enhancement in the levels of BAP, BMD hip, and BMD spine. These results supported the preventive effects of moderate exercise in healthy subjects against osteoporosis. In both sexes, the changes in serum trace elements significantly correlated (P<0.05) with the improvement in BAP, BMD hip, BMD spine, and body mass index in all groups.Conclusion: The observed changes in the levels of Ca, Mn, Cu, and Zn were shown to be positively correlated with improved bone mass density among control and osteoporosis subjects of both sexes. These results demonstrate that aerobic exercise of moderate intensity might protect bone and cartilage by regulation of body trace elements which are involved in the biosynthesis of bone matrix structures and inhibition of bone resorption process via a proposed anti-free radical mechanism. Keywords: essential minerals, osteoporosis, bone density, aerobic exercise, BMD, bone metabolism